Bone Mineral Density and Depression in Premenopausal Women with Primary Fibromyalgia Syndrome - Berna Tander; Yeşim Akyol; Dilek Durmuş; Gamze Alaylı; Kıvanç Cengiz; İlker İlhanlı and Yasemin Ulus and Ferhan Cantürk (Archives of Rheumatology, 2010)
Objective: Sedentary lifestyle, depression and lack of physical activity may lead to a decrease in bone mineral density (BMD) in patients with fibromyalgia syndrome (FMS). The aim of this study was to evaluate the role of FMS in the development of osteoporosis and the impact of depression on the BMD. Materials and Methods: Fifty premenopausal women with a diagnosis of FMS according to the American College of Rheumatology (ACR) criteria and 40 premenopausal healthy controls were included in the study. A structured form was prepared covering demographic characteristics of the subjects. The severity of pain, disease activity and depression level were evaluated by Visual Analog Scale (VAS), Fibromyalgia Impact Questionnaire (FIQ) and Beck Depression Inventory (BDI), respectively. Lumbar spine and left femoral neck BMD values were determined by dual energy X-ray absorptiometry (DEXA). Results: There was no difference between patients and controls according to age, body mass index and duration of education (p>0.05). BMD values in the lumbar vertebrae were significantly lower in the FMS group than in the controls (p<0.05). The BMD score was not different between the patients with a depression score higher or lower than the cut-off point (p>0.05). There were no correlations among BMD, age, and BDI, VAS, and FIQ scores (p>0.05). Conclusion: We found that BMD of the lumbar vertebrae was lower in FMS patients than in the control group. We detected that depression has no significant impact on BMD. (Turk J Rheumatol 2010; 25: 105-9)